Hadith #319 - Sahih al-Bukhari - Zaynab bint Abi Salamah (Sahih al-Bukhari)
Um-Salama said, “I got my menses while I was lying with the Prophet (ﷺ) under a woolen sheet. So I slipped away, took the clothes for menses and put them on. Allah’s Messenger (ﷺ) said, ‘Have you got your menses?’ I replied, ‘Yes.’ Then he called me and took me with him under the woolen sheet.” Um Salama further said, “The Prophet (ﷺ) used to kiss me while he was fasting. The Prophet (ﷺ) and I used to take the bath of Janaba from a single pot.”
Grade: Sahih

Hadith #1241 - Sahih al-Bukhari - Zaynab bint Abi Salamah (Sahih al-Bukhari)
When the news of the death of Abu Sufyan reached from Sham, Um Habiba on the third day, asked for a yellow perfume and scented her cheeks and forearms and said, “No doubt, I would not have been in need of this, had I not heard the Prophet (ﷺ) saying: “It is not legal for a woman who believes in Allah and the Last Day to mourn for more than three days for any dead person except her husband, for whom she should mourn for four months and ten days.”
Grade: Sahih

Hadith #1242 - Sahih al-Bukhari - Zaynab bint Abi Salamah (Sahih al-Bukhari)
I went to Um Habiba, the wife of Prophet, who said, “I heard the Prophets saying, ‘It is not legal for a woman who believes in Allah and the Last Day to mourn for any dead person for more than three days except for her husband, (for whom she should mourn) for four months and ten days’.” Later I went to Zainab bint Jahsh when her brother died; she asked for some scent, and after using it she said, “I am not in need of scent but I heard Allah’s Messenger (ﷺ) saying, ‘It is not lega
Grade: Sahih

Hadith #3190 - Sahih al-Bukhari - Zaynab bint Abi Salamah (Sahih al-Bukhari)
Um Salama said, “Um Sulaim said, ‘O Allah’s Messenger (ﷺ)! Allah does not refrain from saying the truth! Is it obligatory for a woman to take a bath after she gets nocturnal discharge?’ He said, ‘Yes, if she notices the water (i.e. discharge).’ Um Salama smiled and said, ‘Does a woman get discharge?’ Allah’s Apostle said. ‘Then why does a child resemble (its mother)?”
Grade: Sahih